2020
DOI: 10.1038/s41598-020-59598-9
|View full text |Cite
|
Sign up to set email alerts
|

Pool walking may improve renal function by suppressing the renin-angiotensin-aldosterone system in healthy pregnant women

Abstract: This study aimed to examine the effect of pool walking on renal function in pregnant women. Fifteen pregnant women (mean gestational age, 37.8 weeks) walked in a pool (depth 1.3 m) for 1 h. A few days later, they walked on a street for 1 h. Within each activity, the starting and ending levels of plasma renin activity were measured. The total urine volume, creatinine clearance, and change in plasma renin activity levels between each activity were compared by Wilcoxon rank-sum test. The renin-angiotensin-aldoste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… 11 12 Although the biological and genetic pathways (eg, CYP2A6 and nicotine) underlying the associations observed in different phenotypes of HDP (eg, pre-eclampsia and gestational hypertension) have not been elucidated, 20 HDP is recognised as a systemic disease attributable to placental circulatory dysfunction. 21 In experimental research, aerosol from HTPs was found to damage vascular endothelial function in rats. 6 Therefore, the association between HDP risk and HTP use may involve acute and chronic vascular damage, irrespective of combustible cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“… 11 12 Although the biological and genetic pathways (eg, CYP2A6 and nicotine) underlying the associations observed in different phenotypes of HDP (eg, pre-eclampsia and gestational hypertension) have not been elucidated, 20 HDP is recognised as a systemic disease attributable to placental circulatory dysfunction. 21 In experimental research, aerosol from HTPs was found to damage vascular endothelial function in rats. 6 Therefore, the association between HDP risk and HTP use may involve acute and chronic vascular damage, irrespective of combustible cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Although the biological and genetic pathways (e.g., CYP2A6 and nicotine) underlying the associations observed in different phenotypes of HDP (e.g., preeclampsia and gestational hypertension) have not been elucidated, [21] HDP is recognized as a systemic disease attributable to placental circulatory dysfunction. [22] In experimental research, aerosol from HTPs was found to damage vascular endothelial function in rats. [5] Therefore, HDP risk associated with HTP use may involve acute and chronic vascular damage, irrespective of combustible cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%